The Adhesion Syndrome - Backman, H.A. (Canadian Journal of Optometry, 2021)
Rigid gas permeable contact lenses may adhere to the corneal epithelium. Reports of adhesion have been described with only one type of lens material. This report describes three types of lens materials, lens fitting characteristics and the interactions between the eyelid, cornea and contact lens. Various factors may be responsible for the adhesion phenomenon.